Proceedings of the ACM International Conference Companion on Object Oriented Programming Systems Languages and Applications Com 2010
DOI: 10.1145/1869542.1869596
|View full text |Cite
|
Sign up to set email alerts
|

Translucid contracts for modular reasoning about aspect-oriented programs

Abstract: Several proposals have advocated notion of aspect-oriented (AO) interfaces to solve modular reasoning problems, but have not shown how to specify these interfaces to facilitate modular reasoning. Our work on translucid contracts shows how to specify AO interfaces which allow modular understanding and enforcement of control flow interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Leavens, I helped developed the notion of translucid contracts [6,7] that are a greybox specification mechanism for reasoning about implicit invocation systems [29,44]. We showed that translucid contracts enabled modular reasoning about these kinds of systems, which was thought to be a challenge.…”
Section: Translucid Contractsmentioning
confidence: 99%
See 1 more Smart Citation
“…Leavens, I helped developed the notion of translucid contracts [6,7] that are a greybox specification mechanism for reasoning about implicit invocation systems [29,44]. We showed that translucid contracts enabled modular reasoning about these kinds of systems, which was thought to be a challenge.…”
Section: Translucid Contractsmentioning
confidence: 99%
“…7 shows a simple class and its corresponding duck future.Translating a system to Java Translating a system to Java is much simpler than translating a capsule to Java. A system is the sole entry point for a Panini program and it is translated into a single class with the public static void main(String []) method needed to make the class executable in a JVM.Figure 2.8 shows a basic system and its corresponding translation into Java.…”
mentioning
confidence: 99%